The socio-cultural structure of the XIX century Ottoman Empire and translations from this period - Anamur, Hasan (EDITIONS SEDES, 2006)
An unexpected form of westernization can be observed from the last quarter of the XVIIIth century on the Ottoman Empire's life which was considered until this period as an unbroken formation situated at the opposite side of the Christian Europe. From that date were created in that Empire military, engineering, medical academies according to the European models. In 1839 was decreed structural reforms inspired by the French Revolution to reorganise legislative, economical, political and socio-cultural areas. In the second half of the XIXth century, as one of the consequences of this reforms, begin to appear translations from the literature of western Europe, especially from French writers. We propose in this article to study the Ottoman Empire during this century through translations which seem to be caracteristical signs of this socio-cultural metamorphosis.
Keywords: Literature